Effects of exercise on circulating tumor cells among patients with resected stage I-III colon cancer. - Justin C Brown (PLoS ONE, 2018)
BACKGROUND:Physical activity is associated with a lower risk of disease recurrence among colon cancer patients. Circulating tumor cells (CTC) are prognostic of disease recurrence among stage I-III colon cancer patients. The pathways through which physical activity may alter disease outcomes are unknown, but may be mediated by changes in CTCs. METHODS:Participants included 23 stage I-III colon cancer patients randomized into one of three groups: usual-care control, 150 min∙wk-1 of aerobic exercise (low-dose), and 300 min∙wk-1 of aerobic exercise (high-dose) for six months. CTCs from venous blood were quantified in a blinded fashion using an established microfluidic antibody-mediated capture device. Poisson regression models estimated the logarithmic counts of CTCs. RESULTS:At baseline, 78% (18/23) of patients had ≥1 CTC. At baseline, older age (-0.12±0.06; P = 0.04), lymphovascular invasion (0.63±0.25; P = 0.012), moderate/poor histology (1.09±0.34; P = 0.001), body mass index (0.07±0.02; P = 0.001), visceral adipose tissue (0.08±0.04; P = 0.036), insulin (0.06±0.02; P = 0.011), sICAM-1 (0.04±0.02; P = 0.037), and sVCAM-1 (0.06±0.03; P = 0.045) were associated with CTCs. Over six months, significant decreases in CTCs were observed in the low-dose (-1.34±0.34; P<0.001) and high-dose (-1.18±0.40; P = 0.004) exercise groups, whereas no significant change was observed in the control group (-0.59±0.56; P = 0.292). Over six months, reductions in body mass index (-0.07±0.02; P = 0.007), insulin (-0.08±0.03; P = 0.014), and sICAM-1 (-0.07±0.03; P = 0.005) were associated with reductions in CTCs. The main limitations of this proof-of-concept study are the small sample size, heterogenous population, and per-protocol statistical analysis. CONCLUSION:Exercise may reduce CTCs among stage I-III colon cancer patients. Changes in host factors correlated with changes in CTCs. Exercise may have a direct effect on CTCs and indirect effects through alterations in host factors. This hypothesis-generating observation derived from a small pilot study warrants further investigation and replication.